I Can Feel What You Feel: Emotion Exchanges in Twitter Conversations between Candidates and the Public. Issue 2 (20th May 2022) - Paul, Newly; Sui, Mingxiao
Abstract : Twitter offers politicians a direct path of communication to the public, and by its very nature, encourages tweets that are often heavy on emotions. Given the rise of Twitter and emotional appeals in politics, this paper investigates two important questions: How "emotional" are political candidates on Twitter, and, how does the public respond to candidates' tweets containing emotional appeals such as joy, fear, anger, and disgust? Based on Crimson Hexagon's sentiment analysis of over 500, 000 tweets for 541 members of the 115th Congress and the public's corresponding replies, we find that the tone of candidates' tweets and the public's reactions is primarily positive. We also find congruence in the emotions between a political tweet and its reply.